2020
DOI: 10.21608/jappmu.2020.130060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition Vitamin C and Zinc Chloride in Vitrification Medium on Viability, in vitro Maturation and Ultrastructure Changes of Vitrified Immature Bovine Oocytes

Abstract: This study aimed to evaluate the impact of adding vitamin C and zinc chloride to vitrification medium on viability in vitro maturation and ultrastructure changes of vitrified immature Baladi cow oocytes. Compact cumulus oocytes (COCs) (n=1370) were obtained from slaughtered bovine ovaries. Then the morphology of oocytes was examined using a stereomicroscope. Staining with trypan, the in vitro maturation and ultrastructural changes were studied. The results revealed significant (P<0.05) increase of total and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition, there are many cryoprotectants (20% DMSO, 20% EG) in vitrification medium that could negatively affect oocyte viability. Furthermore, Yassen et al (2020) reported that the survival rate, morphological characteristics, and ultrastructural quality were all improved when vitamin C or zinc chloride was added to the vitrification medium in bovine oocytes. These findings are consistent with the role of ascorbic acid in the reduction of abnormalities observed in the present results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are many cryoprotectants (20% DMSO, 20% EG) in vitrification medium that could negatively affect oocyte viability. Furthermore, Yassen et al (2020) reported that the survival rate, morphological characteristics, and ultrastructural quality were all improved when vitamin C or zinc chloride was added to the vitrification medium in bovine oocytes. These findings are consistent with the role of ascorbic acid in the reduction of abnormalities observed in the present results.…”
Section: Discussionmentioning
confidence: 99%